Uterine Fibroids in Pregnancy - Maimoona Qadir Khan; Zubeida Akhtar; Jamila M. Naib (Gandhara University, 2022)
OBJECTIVES: To determine the maternal and fetal outcomes associated with uterine fibroids in pregnancy. METHODOLOGY: This study was conducted in the Gynaecology Department of Mardan Medical Complex from January 2018 to December 2019. All pregnant women of any age or parity or gestational age with sonographic evidence of uterine fibroids were included. Demographic details, gestational age, symptoms related to fibrosis, size, number and location of the fibroid, mode of delivery, antenatal, intrapartum and postnatal complication, and neonatal outcome were entered in a predesigned proforma.   RESULTS:   The incidence of uterine fibroids in pregnancy was 0.8%.77 patients were enrolled. The mean age was 26.5 + 3.22 years. The mode of delivery was a caesarean section in 32.4%, and vaginal delivery in 53% of patients.14% of patients miscarried. Fibroids were multiple in 58.4% and single in 41.5% of patients. Submucosal fibroids were seen in 23%, intramural in 18% and subserosal in 58% of cases. The most common maternal complication was abdominal pain (25%), followed by postpartum haemorrhage(23%) and antepartum haemorrhage(19%). Neonatal outcome was good, with 57% of babies being healthy and 9% being admitted to the Neonatal Intensive Care Unit (NICU) and discharged later. CONCLUSION: Pregnant women with fibroids should be cautiously screened during antenatal to avoid obstetric complications.